Myocardial Protection in Minimally Invasive Mitral Valve Surgery: Comparison of the Cold-Blood Cardioplegia of the Bretschneider Solution and the Warm-Blood Cardioplegia of the Calafiore Protocol - Inna Kammerer; Ragi Nagib; Gernot Hipp; Markus Pre and szlig;mar; Mathias Hansen; Ulrich FW Franke (Archives of Clinical and Experimental Surgery, 2012)
Objective: Minimal invasive mitral valve surgery using right thoracotomy is becoming a safe alternative and has an increasing impact in the clinical routine. The best strategy for myocardial protection for these patients is under discussion. Warm-blood cardioplegia, according to the protocol of Calafiore (group C), is well-established in coronary surgery throughout Europe, whereas the cold-crystalloid cardioplegia by Bretschneider (Custodiol and reg;, group B) is in worldwide use in both heart surgery and organ transplantation. Methods: All 107 patients with proposed mitral valve surgical repair through a right lateral mini-thoracotomy between July 2008 and September 2009 were evaluated and randomly selected for one of the two myocardial protection strategies described above. The quality of the myocardial protection was detected using the specific ischaemia markers cTNI and CK-MB on days zero, one and two following surgery. The study population represents 80% of all patients with isolated mitral surgery from the department. Demographic, as well as operative, data did not show any differences between the groups, and the hospitalization period was 13 days for both groups. Results: The totally clinical mortality rate was 5% (2 patients in group B vs. 3 patients in group C, p=0.673). cTNI >10 and #956;g/l levels 48 hours after the surgical procedure (p=0.055) were significantly higher in group C compared to group B, calculated by ANOVA for repeated measurement using SPSS and reg; 17.0 software. However, the need for defibrillation was higher after Bretschneider`s cardioplegia (45% vs 10%, p<0,001), and heart arrest in the Calafiore group was attained at an average of nine seconds earlier. An IABP was implanted in one patient from the Calafiore group. Conclusions: This prospective study suggests the superiority of myocardial protection using Bretschneider`s cold-crystalloid solution, compared to warm-blood cardioplegia using the Calafiore protocol in minimally invasive mitral valve surgery. [Arch Clin Exp Surg 2012; 1(1.000): 14-21]